"This Is Going to Affect Our Lives": Exploring Huu-ay-aht First Nations, the Government of Canada and British Columbia's New Relationship Through the Implementation of the Maa-nulth Treaty. Issue 3 (27th December 2018) - Sloan Morgan, Vanessa; Castleden, Heather; ,
Abstract: Canada celebrated its 150th anniversary since Confederation in 2017. At the same time, Canada is also entering an era of reconciliation that emphasizes mutually respectful and just relationships between Indigenous Peoples and the Crown. British Columbia (BC) is uniquely situated socially, politically, and economically as compared to other Canadian provinces, with few historic treaties signed. As a result, provincial, federal, and Indigenous governments are attempting to define 'new relationships' through modern treaties. What new relationships look like under treaties remains unclear though. Drawing from a comprehensive case study, we explore Huu-ay-aht First Nations—a signatory of the Maa-nulth Treaty, implemented in 2011—BC and Canada's new relationship by analysing 26 interviews with treaty negotiators and Indigenous leaders. A disconnect between obligations outlined in the treaty and how Indigenous signatories experience changing relations is revealed, pointing to an asymmetrical dynamic remaining in the first years of implementation despite new relationships of modern treaty. Résumé: Le Canada a célébré le 150 e anniversaire de la Confédération en 2017. Parallèlement, le Canada s'engage actuellement dans une ère de réconciliation promouvant la mise en place de relations justes et respectueuses entre les peuples autochtones et la Couronne. La Colombie-Britannique (CB) qui a une position unique, par rapport aux autres provinces canadiennes, sur le plan social, politique et économique n'a ratifié que peu de traités historiques. Conséquemment, les gouvernements provinciaux et fédéraux ainsi que les autochtones tentent de définir de « nouvelles relations » par le biais de traités modernes. Les nouvelles relations qui apparaissent sous ces traités demeurent toutefois imprécises. À partir d'une étude de cas, nous explorons la nouvelle relation entre la CB, le Canada et les Premières Nations Huu-ay-aht – signataires du Traité Maa-nulth mis en œuvre en 2011– en analysant 26 entrevues réalisées auprès des négociateurs du traité et des dirigeants autochtones. Une rupture entre les obligations énoncées dans le traité et la manière dont les signataires autochtones expérimentent les relations changeantes est mise en exergue; une rupture qui laisse entrevoir un maintien de la dynamique asymétrique au cours des premières années de la mise en œuvre du traité, et ce, malgré les nouvelles relations des traités modernes.